Impact of Continuous Two-Team Approach in Autologous Breast Reconstruction - Bauermeister, A. J.; Zuriarrain, A.; Newman, M.; Earle, S. A.; Medina, M. A., III (Journal of Reconstructive Microsurgery, 2017)
Background Autologous breast reconstruction has been noted in the literature to provide superior aesthetic outcomes and patient satisfaction. Additionally, free perforator flap tissue transfer has the potential for lower abdominal donor site morbidity. However, it has been noted that the percentage of women who are undergoing autologous breast reconstruction in the United States is decreasing. Factors related to the technical difficulty, prolonged operative times, and decreasing reimbursement have been implicated as the causes.Methods A retrospective review of electronic medical records over a 5-year period was performed with evaluation of 77 autologous breast reconstructions at a single institution. Patient demographics, comorbidities, number of surgeons involved, operative times, length of stay, and postoperative complications were measured. Wilcoxon rank-sum, Pearson's chi-squared, and proportional odds likelihood ratio tests were performed to compare continuous, categorical, and ordinal outcomes, respectively. Propensity score weighting was used to adjust for presurgical covariates and laterality.Results Operative time and length of stay were both significantly lower in the two- versus the single-microsurgeon groups in the unadjusted setting. When covariates and laterality were adjusted for, operative times still remained significantly shorter in the two-microsurgeon group; there were no differences in complications.Conclusion Based on our findings, we propose that the two-microsurgeon approach can be utilized in more time-consuming microsurgical cases, such as autologous breast reconstruction, to safely decrease operative times and potentially alleviate surgeon fatigue, reduce operative costs, and thus increase overall surgeon productivity.
Keywords: two-microsurgeon; autologous breast reconstruction; free flap